Generational rights and its relationship to sustainable development - Falah, Hasan; AbdulAmeer, Hussam (Journal of Legal Sciences, 2022)
The environment, in its various aspects, is the center of international concern, as it constitutes a common heritage of all humanity, as it has become a common denominator in relation to various issues and problems of an economic, social and cultural nature, and due to the development of public international law, new concepts have emerged that were not previously noticed as the concept of the rights of future generations, As this concept is closely related to the protection of the environment and reality in the field of environmental law, the idea of ​​the rights of future generations has been explicitly defined, especially in international law that is formed with the idea of ​​a common heritage of humanity that must be preserved and inherited in the best conditions for future generations.In addition, the concept of the rights of future generations in international environmental law is linked to the concept of sustainable development is a new civilized method that aims to achieve long-term development, as it is based on environmental balance, environmental safety and preserving natural resources in order to achieve the well-being of current generations while ensuring the rights of future generations, It also imposes the promotion of cooperation opportunities, the renunciation of risks, the challenges of conflict, and concern in protecting what is shared between generations, which is of great importance from the perspective of the future, considering that the rights of future generations are an integral part of human rights, and he emphasized the rights of generations a long time ago in the preamble of the Universal Declaration Human Rights in 1948 to recognize the inherent dignity of all members of the human family, which shows that these rights do not extend to a particular generation, but to all present and future generations.